2018
DOI: 10.1002/slct.201801140
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Copper Nanoparticles Catalyzed Selective Oxidation Reactions: Efficient Catalysis at Room Temperature

Abstract: Bimetallic nanoparticles (NPs) play a pivotal role in promoting high activity and selectivity towards various industrially important reactions in comparison to single metal NPs due to their modulated electronic and surface properties. Herein, we report the synthesis of non‐precious CoCu NPs, which serve as an excellent catalyst for the selective oxidation of a wide range of electronically diverse benzyl alcohols to benzaldehydes, in the presence of tert‐butyl hydroperoxide (TBHP) as an oxidant at room temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Whereafter, this catalytic system was proceeded under O 2 and N 2 atmospheres, respectively, but no obvious difference could be observed, which indicated that O 2 molecules did not participate in the process (Table S5, entries 1–3). On the basis of the observations above, a possible reaction mechanism in Scheme was proposed according to the literatures . Initially, TBHP ( t BuOOH) reacted with Cu sites of POM-Cu­(Ι) catalyst in a so-called Haber–Weiss catalytic mechanism, resulting in a transformation from t BuOOH into tert -butoxyl ( t BuO·) radical and hydroxyl ion (OH – ). , Subsequently, accompanied by the leaving of a t BuOH, the generated t BuO· interacted with 1-phenylethanol to form the radical ( 1 ), which would convert into the intermediate ( 2 ) with the effect of Cu­(ΙΙ) sites in HENU-1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereafter, this catalytic system was proceeded under O 2 and N 2 atmospheres, respectively, but no obvious difference could be observed, which indicated that O 2 molecules did not participate in the process (Table S5, entries 1–3). On the basis of the observations above, a possible reaction mechanism in Scheme was proposed according to the literatures . Initially, TBHP ( t BuOOH) reacted with Cu sites of POM-Cu­(Ι) catalyst in a so-called Haber–Weiss catalytic mechanism, resulting in a transformation from t BuOOH into tert -butoxyl ( t BuO·) radical and hydroxyl ion (OH – ). , Subsequently, accompanied by the leaving of a t BuOH, the generated t BuO· interacted with 1-phenylethanol to form the radical ( 1 ), which would convert into the intermediate ( 2 ) with the effect of Cu­(ΙΙ) sites in HENU-1 .…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of alcohols into carbonyl compounds is a frequently important research topic in the laboratory, for aldehyde/​ketone products take up the key position in the chemical industry including the fine chemical and pharmaceutical industry. , Traditionally, various stoichiometric amounts of oxidizing agents (e.g., MnO 2 , CrO 3 , SeO 2 , KMnO 4 , K 2 Cr 2 O 7 , etc.) have been widely used in industry but under severe conditions such as high pressure or temperatures and/or with strong mineral acids . Also, a mass of environmentally harmful toxic inorganic salts is usually generated from these chemical transformations .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with above oxidants, tert -butyl hydroperoxide (TBHP) is an alternative suitable oxidant and widely used in oxidation reactions, particularly in olefin epoxidation (Chen and Luck, 2016; Kashani et al, 2018) and C–H bond oxidation (Murahashi et al, 2000; Kudrik and Sorokin, 2017; Sarma et al, 2018). There are also some successful examples of using TBHP as an external oxidant in alcohol oxidation (Sarkar et al, 2014; Annunziata et al, 2018; Borah et al, 2018). In spite of this progress, less attention has been paid to this research area.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the copper silicates promoted tBuOOH activation, which may give tert-butylperoxyl, tert-butoxyl and hydroxyl radicals (Equations 1, 2), [35][36][37][38][39] in line with different transitions metal-catalysed peroxidative oxidation reactions. [40][41][42] The radicals may react with BzOH (RCH 2 -OH in Equations 3, 4) giving benzyl alcohol radicals (RCH · -OH in Equations 5-7), [18,38,43] and subsequently BzAld (RCHO). [38,43] According to the literature for BzOH reaction with molecular oxygen, BzOH inhibits BzAcid formation.…”
Section: Catalytic Activity and Mechanistic Insightsmentioning
confidence: 99%
“…[40][41][42] The radicals may react with BzOH (RCH 2 -OH in Equations 3, 4) giving benzyl alcohol radicals (RCH · -OH in Equations 5-7), [18,38,43] and subsequently BzAld (RCHO). [38,43] According to the literature for BzOH reaction with molecular oxygen, BzOH inhibits BzAcid formation. [44] Since considerable amounts of BzAcid were formed in the presence of the copper silicates, one may neglect the influence of molecular oxygen in BzAcid formation.…”
Section: Catalytic Activity and Mechanistic Insightsmentioning
confidence: 99%